Biosynthesis and polyketide oxidation of Monascus red pigments in an integrated fermentation system with microparticles and surfactants. (15th November 2022) - Huang, Zhenfeng; Hu, Tingting; Liu, Haiqing; Xie, Huixin; Tian, Xiaofei; Wu, Zhenqiang
Highlights: Integrated fermentation system (IFS) was established with microparticle & surfactant. IFS improved Monascus mycelial morphology and membrane permeability. Triton X-100 induced the polyketide oxidation of monascopyridine A and B. Increasing respiratory and antioxidase activities promoted pigment biosynthesis. IFS up-regulated genes expression for red pigments biosynthesis. Abstract: Monascus red pigments are widely used in the food industry, mainly as intracellular red pigments. The low yields of extracellular red pigments (ERPs) make them unsuitable for large-scale industrial production. Herein, a novel integrated fermentation system (IFS) consisting of sodium starch octenyl succinate and Triton X-100 was explored for increasing yield, resulting in an ERP yield of 126.7 U/mL, 82.6% higher production than controls (69.4 U/mL). Major ERP components in control fermentations were monascopyridine A and monascopyridine B, but dehydro derivatives, rubropunctamine and monascorubramine, predominated in the test fermentations, presumably due to polyketide oxidation induced by Triton X-100. Improvement of hyphal morphology, membrane permeability, respiratory activity, and gene expression for red pigment biosynthesis is likely to be critical to increase yield and change the compositions. This study provides an effective strategy to accelerate the biosynthesis and secretion of Monascus pigments.